ANALISIS DAMPAK CAT CALLING TERHADAP PEREMPUAN DI RUANG PUBLIK: PERSPEKTIF PSIKOLOGIS DAN SOSIAL - Vita Febriyanti; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study aims to analyze the impact of cat calling on women in public spaces, focusing on the psychological and social effects of such actions. The research employs a qualitative approach with in-depth analysis of content from various related literatures to explore women's perceptions of cat calling and its effects on their daily lives. The primary focus of this study is on the psychological and social consequences, such as anxiety, stress, and discomfort experienced by women when encountering cat calling, which subsequently affects their self-confidence and the quality of their social relationships. These psychological effects not only harm women's mental well-being but also exacerbate their emotional state when interacting with their social environment. The research findings indicate that cat calling has a significant negative impact on women's psychological and social well-being. Therefore, this study emphasizes the importance of prevention efforts and public education to reduce this practice, in order to make public spaces safer and more comfortable for women